Antimicrobial resistance of Enterobacteriaceae in rabbit farms: an underestimated reservoir harboring mcr-1.1 - Hu, Zizhe; Chen, Dongdong; Shi, Tuanyuan; Huang, Yee; Cui, Xuemei; Li, Xiaoyu; Ji, Quanan; Bao, Guolian; Liu, Yan (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe transmission of antimicrobial resistance (AMR), particularly the antimicrobial resistance gene in Enterobacteriaceae, presents a critical challenge to global public health. Sichuan province is the largest producer and consumer of rabbit meat in China. However, few studies have focused on AMR surveillance in rabbits.MethodsEnterobacteriaceae strains were isolated and identified by MALDI-TOF. The minimum inhibitory concentration (MIC) was determined according to the Clinical and Laboratory Standards Institute. Whole-genome sequencing was performed using the Illumina and Oxford Nanopore Technologies (ONT) platforms.Results and discussionA total of 73 Enterobacteriaceae strains were isolated, including Klebsiella pneumoniae, Salmonella enterica, Enterobacter hormaechei, and Escherichia coli. Resistance rates to tetracycline, ciprofloxacin, nalidixic acid, sulfamethoxazole-trimethoprim, and ampicillin exceeded 60%. For Escherichia coli isolates showed that ST328, ST22, and ST29 were the primary sequence types, with O178:H7 being the predominant serotype. Remarkably, 48% (35/73) of the isolates carried the mcr-1.1 gene, and among these, 82.9% (29/35) mcr-1.1-positive isolates contained the IncI2 plasmid replicon. The mcr-1.1 gene in Klebsiella pneumoniae, Salmonella enterica and Escherichia coli transferred to a recipient strain. Furthermore, the genetic environment of the mcr-1.1 gene showed that it was flanked by PAP2 and a relaxase. Comparative analysis indicated that the mcr-1.1-positive plasmid exhibited high sequence identity to plasmids from human, porcine, and bovine sources. Notably, a phylogenetic analysis based on core single nucleotide polymorphisms demonstrated that certain rabbit-derived mcr-1-positive Escherichia coli strains clustered within the same evolutionary branch as humanderived strains. These findings indicated that smaller-scale breeding operations, such as rabbit farming, could serve as underrecognized reservoirs of AMR determinants, particularly the mcr-1.1 gene, thus requiring systematic assessment.